Lactoferricin Peptides Increase Macrophages' Capacity To Kill Mycobacterium avium - Silva, T (2017)
Mycobacterial infections cause a significant burden of disease and death worldwide. Their treatment is long, toxic, costly, and increasingly prone to failure due to bacterial resistance to currently available antibiotics. New therapeutic options are thus clearly needed. Antimicrobial peptides represent an important source of new antimicrobial molecules, both for their direct activity and for their immunomodulatory potential. We have previously reported that a short version of the bovine antimicrobial peptide lactoferricin with amino acids 17 to 30 (LFcin17-30), along with its variants obtained by specific amino acid substitutions, killed Mycobacterium avium in broth culture. In the present work, those peptides were tested against M. avium living inside its natural host cell, the macrophage. We found that the peptides increased the antimicrobial action of the conventional antibiotic ethambutol inside macrophages. Moreover, the d-enantiomer of the lactoferricin peptide (d-LFcin17-30) was more stable and induced significant killing of intracellular mycobacteria by itself. Interestingly, d-LFcin17-30 did not localize to M. avium-harboring phagosomes but induced the production of proinflammatory cytokines and increased the formation of lysosomes and autophagosome-like vesicles. These results lead us to conclude that d-LFcin17-30 primes macrophages for intracellular microbial digestion through phagosomal maturation and/or autophagy, culminating in mycobacterial killing. IMPORTANCE The genus Mycobacterium comprises several pathogenic species, including M. tuberculosis, M. leprae, M. avium, etc. Infections caused by these bacteria are particularly difficult to treat due to their intrinsic impermeability, low growth rate, and intracellular localization. Antimicrobial peptides are increasingly acknowledged as potential treatment tools, as they have a high spectrum of activity, low tendency to induce bacterial resistance, and immunomodulatory properties. In this study, we show that peptides derived from bovine lactoferricin (LFcin) improve the antimicrobial activity of ethambutol against Mycobacterium avium growing inside macrophages. Moreover, the d-enantiomer of a short version of lactoferricin containing amino acids 17 to 30 (d-LFcin17-30) causes intramacrophagic death of M. avium by increasing the formation of lysosomes and autophagosomes. This work opens the way to the use of lactoferricin-derived peptides to treat infections caused by mycobacteria and highlights important modulatory effects of d-FLcin17-30 on macrophages, which may be useful under other conditions in which macrophage activation is needed.